Formylpeptide receptors in GtoPdb v.2021.2. (2021) - Bäck, Magnus; Boulay, François; Chiang, Nan; Dahlén, Sven-Erik; Dahlgren, Claes; Drazen, Jeffrey; Evans, Jilly F.; Gerard, Craig; Murphy, Philip M.; Parmentier, Marc; Quinn, Mark; Rovati, G. Enrico; et al.
No abstract available